PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA MATERI PECAHAN MELALUI VIRTUAL SMART FRACTION BERBASIS ADOBE FLASH - Giyanto Giyanto; Abdul Ghoni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study was initiated by the fact that Elementary schools (SD/MI) teachers did not utilize learning media optimally, especially interactive media, in learning fractions. Meanwhile, nowadays the technology grows rapidly so it requires teachers to be able to adjust themselves in utilizing the technology. Technology brings education to a more advanced and more developed condition in the learning process, both inside and outside the classroom. The purpose of this study was to develop an effective, practical, interactive, and innovative learning media for mathematics learning, especially about fraction. This study was research and development. The results found that Virtual Smart Fraction was very feasible and effective to be used as a learning media. The feasibility of the media was based on the results of validation from media experts with the percentage of 93.33% and from material experts with the percentage of 96.25%. Then, the effectiveness of this media was revealed based on the results of the small group test with a percentage of 96.36% and the results of the large group test with the percentage of 95.14%. Besides, it was also found that Virtual Smart Fraction media increased the average score of the students from 62.58 to 89.82. Thus, Virtual Smart Fraction media was categorized as valid, very feasible, and very effective as a learning media for mathematics learning.